2016
DOI: 10.1194/jlr.m069948
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study of triglyceride postprandial responses to a high-fat dietary challenge

Abstract: Postprandial lipemia (PPL), the increased plasma TG concentration after consuming a high-fat meal, is an independent risk factor for CVD. Individual responses to a meal high in fat vary greatly, depending on genetic and lifestyle factors. However, only a few loci have been associated with TG-PPL response. Heritable epigenomic changes may be significant contributors to the unexplained inter-individual PPL variability. We conducted an epigenome-wide association study on 979 subjects with DNA methylation measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 61 publications
(100 reference statements)
1
30
0
Order By: Relevance
“…Lai et al [ 40 ] showed that eight methylation sites encompassing different genes LPP encoding lipoma-preferred partner, APOA5 encoding apolipoprotein A-V, SREBF1 , ABCG1 , and CPT1A were associated with triglyceride postprandial responses (TG-PPL), an independent CVD risk factor, after consuming a high-fat meal [ 40 ]. These genes had been previously found to be associated with triglyceride and/or HDL-C levels [ 15 , 23 ▪▪ , 24 ▪ , 25 , 38 ▪▪ ].…”
Section: Newly Discovered Cpg Sites and Their Level Of Evidencementioning
confidence: 99%
“…Lai et al [ 40 ] showed that eight methylation sites encompassing different genes LPP encoding lipoma-preferred partner, APOA5 encoding apolipoprotein A-V, SREBF1 , ABCG1 , and CPT1A were associated with triglyceride postprandial responses (TG-PPL), an independent CVD risk factor, after consuming a high-fat meal [ 40 ]. These genes had been previously found to be associated with triglyceride and/or HDL-C levels [ 15 , 23 ▪▪ , 24 ▪ , 25 , 38 ▪▪ ].…”
Section: Newly Discovered Cpg Sites and Their Level Of Evidencementioning
confidence: 99%
“…The GOLDN study was designed with 2 arms: a high-fat meal challenge and fenofibrate treatment for 3 weeks to identify genetic determinants of lipid response to 2 interventions. A total of 1053 individuals met all eligibility requirements, while the data in use for lipids at visits 1 and 2, at the start of the trial, and at visits 3 and 4, at the end of the trial, that have genotype and methylation were smaller [ 8 12 ]. The GAW20 simulated data [ 7 ] followed the structure of real data, by simulating the effects of a lipid-lowering medication in interaction with methylation by affecting TG levels.…”
Section: Methodsmentioning
confidence: 99%
“…The association of DNA methylation at ABCG1 locus in whole blood DNA with plasma TG and HDL-C levels was replicated in several studies recapitulated in Table 1 which were conducted in the Botnia prospective study (cg06500161, TG, n = 258) [ 80 ], the Rotterdam study (cg06500161, TG and HDL-C, n = 1485) [ 78 ], the Framingham heart study (FHS) and prospective investigation of the vasculature in uppsala seniors study (PIVUS) (cg06500161, TG and HDL-C, cg27243685 and cg01176028, TG, n = 2036) [ 79 ] and in Canadian familial hypercholesterolemia patients (CpGC3, TG, HDL-C and TC, n = 98) [ 81 ]. In addition, Lai et al reported that methylation of the ABCG1 CpG site (cg06500161) in blood CD4 + T cells from 979 subjects of the genetics of lipid lowering drugs and diet network (GOLDN) study was significantly associated with postprandial hypertriglyceridemia (PPHT) after consumption of a high-fat test meal [ 82 ]. Indeed, an increased methylation at ABCG1 was correlated with an increased PPHT response.…”
Section: Abcg1 and Lipid Metabolism And Homeostasismentioning
confidence: 99%